On the Establishment of a Precise GPS Network in Khartoum State - A. Mohammed, Mudathir; A. Khalil, Rashad; M. Awadelgeed, Awadelgeed; H. Seedahmed, Gamal (University of Khartoum Engineering Journal, 2022)
The use of the Global Positioning System (GPS) as a fast and efficient alternative in the geodetic network measurements has become a common practice worldwide. The advantages of using the GPS technique compared to the traditional surveying methods are based on accuracy, time and cost. In this study, the static-mode of GPS measurement technique has been utilized to establish a precise geodetic network in Khartoum State. The network was referenced to a single control station that is related to the International Terrestrial Reference Frame (ITRF 2005). A number of six points have been constructed and observed around Khartoum State. In particular, seven observation sessions were conducted that gave an over determined system. The least-squares method was used in the adjustment of the GPS network. Two methods were utilized for the adjustment, namely, the parametric and the condition equation methods. The most probable values of the coordinates of the newly-established points were computed from both methods and they were found to be identical. The average standard deviation of the X, Y, and Z coordinates are ±1.36 cm, ±1.12 cm, & ±0.69 cm respectively.